Supervisees' perceptions of postgraduate supervision in a Malaysian public university / Syuhaidah Mohd Sait - Mohd Sait, Syuhaidah (2015)
This study was conducted with the aim to investigate supervisees' perceptions on postgraduate supervision. The descriptive correlational study comprised 132 postgraduate students from a public university located in the state of Selangor in Malaysia. The study employed a mixed-methods approach where data were collected using a set of questionnaire and semi-structured interviews. The quantitative data were statistically analysed using SPSS version 20 while the qualitative data were analysed using thematic analysis to trace emerging themes. The validity of the instruments was established through experts' opinions meanwhile the overall reliability was established at 0.900 alpha level. The findings revealed that postgraduate students perceived themselves as the most responsible at the proposal stage compared to the other stages of postgraduate study. There were also no significant differences on their perceptions regarding supervisees' roles and responsibilities with regards to gender, mode of study and academic qualifications. The students also highlighted that they need a high level of support from their supervisors in their postgraduate study especially at the proposal and final writing stages, indicating a heavy reliance and dependence on supervisors. There was a significant difference in the level of support needed with regards to respondents' academic qualification but there was significant difference with regards to their gender and mode of study. Moreover, the findings also implied that the postgraduate students were dependent on their supervisors. Yet, the level of relationship between the students and supervisors was at moderate level. There were also no significant differences with regards to gender, mode of study and academic qualification of the supervisees in the student-supervisor relationship. Furthermore the challenges highlighted by students focussed more on their personal limitations which included their lack in-depth reading in their area investigation, followed by lack of research methodology knowledge and lack of self-esteem in conducting research. Based on the findings of this study it is recommended that students be provided with more institutional help to equip them with the necessary research knowledge and skills so that they can be less dependent on supervisors and learn to take ownership of their own study. Nevertheless, steps must also be taken to improve the quality of postgraduate supervision so that students can be nurtured and guided towards successful on-time completion of their research study.